PENGEMBANGAN KONTEN SISTEM PENGELOLAAN PEMBELAJARAN (SIPEJAR) MATAKULIAH DESAIN PEMBELAJARAN ANAK USIA DINI BERBASIS CASE METHOD & TEAM BASED PROJECT - I Wayan Sutama; Wuri Astuti; Pramono; Lailatus S; Dewi Nur’Aini5 (Universitas Pendidikan Ganesha, 2023)
Learning reorientation in PAUD can be done by designing innovative learning. It is just that most PAUD teachers and PGPAUD students have yet to make learning designs that lead to these competencies. This research aims to develop and implement an innovative learning design in a learning management system (SIPEJAR). This research belongs to the type of development research with the ADDIE model. The research population was all PGPAUD FIP UM students, with a sample of 105 people. Data collection used observation, interview, and questionnaire methods, with research instruments in the form of media and material expert test instruments, as well as limited and broad trial instruments. The data obtained in the study were then analyzed using a measure of central tendency (mean) for quantitative data and supplemented with qualitative data in the form of input/suggestions from reviewers/validators and trial participants. The results of the research analysis showed that the media test results obtained 90.38, which was in the very feasible category; the material test results obtained a score of 94.42 which was in the very feasible category; the limited group test results obtained a score of 84.39 which was in the very feasible category, and the results the broad group test obtained a result of 88.92 with a very decent category. Based on these results, SIPEJAR media, based on the case method and team-based project, is very feasible to be developed and taught to students.